WEBSITE BASED PARKING MANAGEMENT INFORMATION SYSTEM CASE STUDY OF THE DARMAJAYA INSTITUTE OF INFORMATICS AND BUSINESS - Halimah, Halimah; Andriyadi, Anggi; Yuliawati, Dona; Lismainy, Eva (Jurnal TAM (Technology Acceptance Model), 2023)
This research aims to design and implement a website-based Parking Management Information System as a case study at the Darmajaya Institute of Informatics and Business. The system developed is able to select parking spaces according to the parking quota provided by the campus. The parking locations provided consist of Canteen Parking Lots, Basketball Court Parking Lots, Futsal Court Parking Lots, Parking Lots in Front of the Mosque, Parking Lots Next to the Basketball Court, and Parking Lots Next to the Futsal Court. In this system, when a vehicle enters, an admin will enter data on the plate number, entry date, parking code, entry time, vehicle type and parking position specified for the vehicle owner. This system helps security guards as parking managers at the Darmajaya Institute of Informatics and Business to carry out parking management well and efficiently, so that the problem of parking overload can be minimized. The results of this research contribute to the development of information technology in parking management in the campus environment. By using this system the parking management process can be more structured and computerized, as well as providing convenience for parking users and parking managers and can increase efficiency and improve services in overcoming parking problems that often occur on campus.